Bitter Orange Aromatherapy: A Natural Solution to Reduce Pain During the First Stage of Labor - Ernawati Anggraeni; Abdillah Fatkhul Wahab; Trisna Pangestuning Tyas; Lailaturohmah (CV. Get Press Indonesia, 2024)
Labor pain is a significant challenge for expectant mothers, affecting both the psychological and physiological aspects of pregnant woman. Non-pharmacological pain management approaches, such as aromatherapy, have gained attention for their effectiveness and minimal side effects. This study aimed to assess the impact of bitter orange aromatherapy on reducing labor pain during the first stage of labor at Inpatient Clinic Pratama Ibu Hawa in 2024. A quasi-experimental design with pre-test and post-test measures was employed, involving 22 multigravida women in active labor. The intervention group received bitter orange aromatherapy via a diffuser for 60 minutes, while the control group received standard care. Pain intensity was measured using the Visual Analog Scale (VAS). The results indicated a significant reduction in pain intensity after the intervention, with a notable shift from moderate to mild pain in the experimental group (p = 0.000, 95% CI = (5.098-8.876). These findings suggest that bitter orange aromatherapy is an effective non-pharmacological intervention for reducing labor pain, improving maternal comfort, and enhancing the overall labor experience. The study highlights the potential for integrating aromatherapy into routine maternal care, offering an accessible and cost-effective alternative to pharmacological methods. Further research is needed to explore its broader application and long-term benefits in various clinical settings.